Terminally exhausted CD8+ T cells in solid tumors: biology, biomarker potential and translational tools for precision oncology - Guo, Xuejun; Ma, Shuhan; Wang, Jingwen; Fu, Yilin; Ma, Wenxue (Frontiers in Immunology, 2026)
Terminally exhausted CD8+ T cells (Ttex) are emerging as clinically relevant immune subsets across solid tumors, marked by sustained inhibitory receptor expression, loss of TCF1, and limited proliferative capacity. Once considered functionally inert, Ttex are now recognized for their residual cytotoxic potential and strong associations with tumor immunogenicity, including microsatellite instability (MSI), high tumor mutational burden (TMB), and neoantigen load. Importantly, the prognostic significance of Ttex is highly tumor-context-dependent, shaped by stromal architecture, mutational burden, and progenitor Tpex availability. This review examines the biology, spatial localization, and prognostic value of Ttex, highlighting the Ttex/CD8+ ratio as a promising biomarker in cancers such as colorectal, lung, and esophageal carcinoma. We summarize recent advances in multiplex imaging, digital pathology, and AI-driven quantification that support the clinical integration of Ttex assessment. In addition, we discuss emerging therapeutic strategies targeting Ttex through immune checkpoint combinations, thymocyte selection-associated high mobility group box protein (TOX) and circRNA-mediated reprogramming, and exhaustion-resistant T cell engineering. Finally, we outline translational priorities including assay harmonization, functional validation, and longitudinal profiling to advance Ttex-based precision oncology.